2015
DOI: 10.1152/ajpcell.00037.2014
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 regulates P2X7receptor signaling in osteoblasts

Abstract: The synthesis of new bone in response to a novel applied mechanical load requires a complex series of cellular signaling events in osteoblasts and osteocytes. The activation of the purinergic receptor P2X7R is central to this mechanotransduction signaling cascade. Recently, P2X7R have been found to be associated with caveolae, a subset of lipid microdomains found in several cell types. Deletion of caveolin-1 (CAV1), the primary protein constituent of caveolae in osteoblasts, results in increased bone mass, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…This venue, however, remains to be explored. Most importantly, our findings are consistent with other studies that have made compelling arguments regarding the existence of purinergic receptors in caveolae consequently providing an enriched environment for integrating necessary interactions for signal transduction (39,79,80).…”
Section: Discussionsupporting
confidence: 91%
“…This venue, however, remains to be explored. Most importantly, our findings are consistent with other studies that have made compelling arguments regarding the existence of purinergic receptors in caveolae consequently providing an enriched environment for integrating necessary interactions for signal transduction (39,79,80).…”
Section: Discussionsupporting
confidence: 91%
“…2b,c arrows). These “clusters” may be located to lipid rafts, as is known to be the case for this receptor 54 , 55 . Furthermore, P2X7R is also found intracellulary in organelles most likely associated with receptor synthesis or endocytosis.…”
Section: Resultsmentioning
confidence: 89%
“…We concluded that shear stress regulation of P2X7 is downstream from transcription or mRNA stability because P2X7 mRNA levels were not enhanced by atheroprone flow (data not shown). Interestingly P2X7 receptors are associated with caveolae in osteoblasts, 27 cardiomyocytes, 28 and alveolar epithelial cells, 29 , 30 while post-translational modifications direct P2X7 to lipid microdomains. 31 Thus we speculate that caveolae, which are shear sensitive, 32 may play a role in atheroprone-mediated up-regulation and clustering of P2X7 at the cell surface thereby enhancing calcium influx and inflammatory signalling in response to ATP.…”
Section: Discussionmentioning
confidence: 99%